UPAYA PENCEGAHAN DAN PENYELESAIAN SENGKETA TANAH MELALUI PENYULUHAN DI DESA BANAGAN - Hairil Hairil; Ahmad Malontu; Irfan Irfan; Nazmi Nazmi; Wirda Wirda; Debi Stafani (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
Land disputes are one of the most common social problems in rural communities, often caused by unclear boundaries, overlapping ownership, inheritance issues, and limited legal awareness regarding land administration. This community service program aimed to provide legal counseling to the people of Banagan Village, Dampal Utara District, as both a preventive and curative effort to address and resolve land disputes. The activity was carried out through legal counseling sessions and interactive discussions involving 50 participants, including village officials, community leaders, and landowners. The results indicate a significant increase in participants’ understanding of land certification, preventive measures, and dispute resolution mechanisms through village deliberation, mediation, and litigation. Based on the pre-test and post-test results, participants’ understanding improved from around 25–40% before the counseling to 70–85% after the activity. These findings confirm that legal counseling is effective in enhancing legal awareness, strengthening the culture of deliberation, and providing preventive solutions to potential social conflicts in rural areas. Therefore, this program makes a tangible contribution to building a more legally conscious, just, and harmonious society.